Relationships Between Childhood Health Experience and Depression Among Older People: Evidence From China - Yao, Min (Frontiers in Psychology, 2021)
The assessment of childhood health experience helps to identify the risk of depression among older people. Poor childhood experience is generally associated with depression in adulthood. However, whether such association can be extended to older people’ life remains unclear. The history of parental mental health was obtained from 2014 CHARLS Wave 3 (Life History Survey) data while other data from 2011 CHARLS Wave 1 baseline data. The study involves 4,306 respondents. The depression was assessed by the Chinese version of Center for Epidemiologic Studies Depression scales (CES-D) using logistic regression model. More than 40% of older people suffered from depression, 25% of whom experienced poor childhood self-reported health. Nearly 20% of their mothers and more than 10% of their fathers had a history of poor mental health. Poor childhood health experiences have shown to be associated with higher odds of depression (good self-reported health OR: 0.732, p = 0.000, 95% CI: 0.633–0.847; poor mother’s mental health OR: 1.391, p = 0.001, 95% CI: 1.138–1.699; poor father’s mental health OR: 1.457, p = 0.003, 95% CI: 1.141–1.862). There is a high rate of depression among the older adults in China. In China, older people with poor childhood health experiences are more likely to suffer from depression.